Lung toxicity of particulates and gaseous pollutants using ex-vivo airway epithelial cell culture systems. (15th July 2022) - Lakhdar, Ramzi; Mumby, Sharon; Abubakar-Waziri, Hisham; Porter, Alexandra; Adcock, Ian M.; Chung, Kian Fan
Abstract: Air pollution consists of a multi-faceted mix of gases and ambient particulate matter (PM) with diverse organic and non-organic chemical components that contribute to increasing morbidity and mortality worldwide. In particular, epidemiological and clinical studies indicate that respiratory health is adversely affected by exposure to air pollution by both causing and worsening (exacerbating) diseases such as chronic obstructive pulmonary disease (COPD), asthma, interstitial pulmonary fibrosis and lung cancer. The molecular mechanisms of air pollution-induced pulmonary toxicity have been evaluated with regards to different types of PM of various sizes and concentrations with single and multiple exposures over different time periods. These data provide a plausible interrelationship between cellular toxicity and the activation of multiple biological processes including proinflammatory responses, oxidative stress, mitochondrial oxidative damage, autophagy, apoptosis, cell genotoxicity, cellular senescence and epithelial-mesenchymal transition. However, these molecular changes have been studied predominantly in cell lines rather than in primary bronchial or nasal cells from healthy subjects or those isolated from patients with airways disease. In addition, they have been conducted under different cell culture conditions and generally in submerged culture rather than the more relevant air-liquid interface culture and with a variety of air pollutant exposure protocols. Cell types may respond differentially to pollution delivered as an aerosol rather than being bathed in media containing agglomerations of particles. As a result, the actual pathophysiological pathways activated by different PMs in primary cells from the airways of healthy and asthmatic subjects remains unclear. This review summarises the literature on the different methodologies utilised in studying the impact of submicron-sized pollutants on cells derived from the respiratory tract with an emphasis on data obtained from primary human cell. We highlight the critical underlying molecular mechanisms that may be important in driving disease processes in response to air pollution in vivo . Highlights: Air-liquid interface epithelial cells are suitable for studying pollution toxicity. Dosimetric exposure and particle size-specificity allow for dose-response analysis. Inflammation, oxidative stress and mitochondrial damage result from pollution toxicity. Personal response to air pollution of nasal epithelium may inform on susceptibility.